PENGARUH KETERAMPILAN PROSES IPA DAN MOTIVASI BELAJAR SISWA TERHADAP KREATIVITAS BELAJAR - Yenita Sandra Sari (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
The aim of this research is to know the influence of skill process in natural science and motivation of students learning toward of students’ creativity. The research method is survey method with correlation technical. The sample is 40 students with simple random technique. The skill process data of natural science is collected by test, while the data of students’ learning motivation and students’ creativity is collected in questionnaire form. The data analysis is done by regression and correlation analysis. The research result is shown that; 1) There is an influence of the skill process in natural science toward learning creativity. 2) There is influence of students learning motivation toward learning creativity. 3) There is an influence the skill process in natural science and students learning motivation together toward students’ creativity.